THE SOCIO-CULTURAL ACTIVITY WITH SCHOOLS AND THE MUSEUM AS A COLLABORATION ENTITY - FILIPSKI, Tatiana (Acta et Commentationes, Sciences of Education, 2020)
The following article represents a study offering a theoretical and practical analysis of some educational aspects and contributes to museum education of students via school – museum – community partnership. In the following study is underlining the importance of educational collaboration, are specified the bounds to museum education; is developed the museum – school partnership possibilities matrix. Meanwhile are described the factors that would support the development and promoting of museum heritage in collaboration between school – museum – community.